Egypt Economic Update, Fall 2010 - World Bank (Washington, DC, 2017)
Egypt's growth accelerated in the second half of FY10. Real Gross Domestic Product (GDP) growth in FY10 reached 5.8 percent, up from 4.4 percent in FY09 and 4.8 percent in FY10, taking up overall GDP growth to an average of 5.3 percent for the full FY10. Egypt's macroeconomic outlook is stable. Assuming that domestic demand holds up, and Egyptian exports continue their observed recent trend, we expect that the Egyptian economy grows in the range of 6.0 to 6.2 percent in FY11. This is underpinned by strong commitment to maintain structural reforms momentum, and a relatively stable global economy. However, unemployment will remain a challenge as growth as high as 6 percent will barely absorb the increasing number of new entrants to the labor market. Unemployment will continue to be an overriding concern and will gradually fall to around 8.7 percent in FY11. Finally, inflationary pressures are expected to rise, as global prices are likely to filter to domestic consumer prices, domestic demand will gain more solid ground, and gradual adjustment of energy prices will be implemented. Interest rates are not thus expected to rise, yet real interest rates will remain low or negative. This outlook is consistent with that of standard and poor's ratings services which affirmed in 2010.